2018
DOI: 10.5765/jkacap.180002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Tools for the Mental Health of School-Aged Children and Adolescents Exposed to Disaster: A Systematic Review (1988-2015)

Abstract: Objectives:In this study, we aimed to conduct a systematic review of studies investigating psychosocial factors affecting children exposed to disasters. Methods: In total, 140 studies were retrieved. The studies were published from 1988 to 2015. A systematic review was performed using the PRISMA guidelines. MEDLINE, EMBASE, Cochrane Central, Web of Science, PsycINFO, PubMed, and Google Scholar were searched. Each database was searched using the following termsThe identified studies were subjected to data extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…When reviewing various studies related to disaster, it was found that the incidence of PTSD showed different results depending on the age of the victim, the timing of the intervention, prior experiences before the traumatic events, and the clinician who performed the evaluation 2829303132. Therefore, we focused on related studies using the measurements used in the clinicians' evaluations and structured or semi-structured interviews with the children and adolescents 33…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing various studies related to disaster, it was found that the incidence of PTSD showed different results depending on the age of the victim, the timing of the intervention, prior experiences before the traumatic events, and the clinician who performed the evaluation 2829303132. Therefore, we focused on related studies using the measurements used in the clinicians' evaluations and structured or semi-structured interviews with the children and adolescents 33…”
Section: Discussionmentioning
confidence: 99%
“…The SDQ questionnaire used in this research was already written in Bahasa and could be accessed freely. The SDQ was chosen as a diagnostic tool because it has been successfully implemented in many Asian countries as one of the most reliable indicators of pediatric mental disturbance (Lee & Bhang, 2018 ; Lieber, 2017 ; McDermott et al, 2005 ). One local study showed that the SDQ has good reliability, with a Cronbach’s alpha of 0.773 (Oktaviana & Wimbarti, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our findings, children's health, as a specific vulnerable group, needs to be assessed in disasteraffected communities. However, the literature has highlighted the assessment of children's mental health issues after disasters rather than their physical health (56)(57)(58)(59) Children experiencing disasters are vulnerable to mental health trauma, particularly in developing countries (16). Thus, providing mental health services for children may be the most important step in the assessment of health system functions after disasters.…”
Section: Environmental Health Training 63mentioning
confidence: 99%